2010
DOI: 10.1590/s1808-86942010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia da laserterapia nas disfunções têmporo-mandibulares: estudo controle

Abstract: Temporomandi bular dysfunction is characterized by the presence of painful joint/muscular symptoms muscle in the face. The main justification for the use of lasers in laser therapy dysfunction is its analgesic effect, which was observed in most studies in the literature. Aim:We evaluated the effectiveness of laser therapy in the treatment of temporomandibular disorders.Methods: 50 volunteers with temporomandibular disorders were divided into two groups (control and experimental) had amplitudes of movements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
0
15
0
4
Order By: Relevance
“…Alterations of neuronal activity in auditory pathways of tinnitus patients have also been documented by using auditory evoked potentials, where both increases (Santos and Matas, 2010) and decreases (Attias et al, 1993, 1996) of amplitudes have been found. The increases were observed in patients without hearing loss (i.e., <25 dB; Santos and Matas, 2010), whereas the decreases in patients with hearing loss (Attias et al, 1993).…”
Section: The Involvement Of Central Auditory Pathways In Tinnitusmentioning
confidence: 91%
See 1 more Smart Citation
“…Alterations of neuronal activity in auditory pathways of tinnitus patients have also been documented by using auditory evoked potentials, where both increases (Santos and Matas, 2010) and decreases (Attias et al, 1993, 1996) of amplitudes have been found. The increases were observed in patients without hearing loss (i.e., <25 dB; Santos and Matas, 2010), whereas the decreases in patients with hearing loss (Attias et al, 1993).…”
Section: The Involvement Of Central Auditory Pathways In Tinnitusmentioning
confidence: 91%
“…The increases were observed in patients without hearing loss (i.e., <25 dB; Santos and Matas, 2010), whereas the decreases in patients with hearing loss (Attias et al, 1993). Significantly increased N1–P2 amplitudes were found at higher stimulus intensities for the tinnitus ear in comparison to the non-tinnitus ear in patients with unilateral tinnitus (Norena et al, 1999).…”
Section: The Involvement Of Central Auditory Pathways In Tinnitusmentioning
confidence: 96%
“…O raio laser pode ser compreendido como uma modalidade de radiação eletromagnética bem peculiar, com propriedades típicas, havendo a diferenciação da luz oriunda por geradores padronizados incandescentes, sendo os tipos, definidos conforme algumas características, como o comprimento da onda, a sua profundidade, assim como a sua devida aplicação (Santos, 2010).…”
Section: Referencial Teóricounclassified
“…Esse método é totalmente indolor e também na apresenta nenhum tipo de queimação. A principal finalidade dessa terapia é proporcionar uma otimização e recuperação em pacientes que se encontram na fase da pós-cirurgia, reduzindo rapidamente os edemas e apresentando melhorias do estado geral do paciente hospitalizado ou que se encontram em recuperação em casa (Santos, 2010).…”
Section: Art 1ºunclassified
“…Por fim, quatorze artigos foram excluídos por não indicarem a faixa etária dos pacientes e/ou por descrever apenas a média de idade dos participantes ou por apresentar pacientes com mais de 55 anos no estudo (MAZZETTO, M.O;HOTTA;PIZZO, 2010;SANTOS et al, 2010;BORGES et al, 2018;MAGRI et al, 2017;DEMIRKOL et al, 2015;AHRARI et al, 2014;MAIA et al, 2014;VENEZIAN et al, 2010;CUNHA et al, 2008;ZANIRATO, 2005;SVESHTAROV et al, 2018;DEMIRKOL et al, 2017;ÇETINER;KAHRAMAN;YÜCETAŞ, 2006;CONTI., 1997), não correspondendo aos critérios de inclusão da pesquisa. Dessa forma, foram incluídos apenas cinco artigos.…”
unclassified